Code Switching on “Catch Me Up!”: A New Style of News Writing? - Wildi Adila; Afika Hany Amaliab; Lina Nur Ainic; Sari Murni; Imaduddin Hanif (University of Surakarta, 2024)
News writing is generally formulated using a standard, formal language style. However, Catch Me Up!, an online daily newspaper, broke those strict rules by offering casual, loose, non-standard language which predominantly used code-switching as one of the ways to alter formal to informal language styles. Hence, this study aimed to describe the various types of code-switching that occurred on Catch Me Up! and explain why the news frequently employed code-switching. Three theories underlie the present research; types of code-switching by Poplack and a combination of reasons for code-switching by Hoffmann, Gumperz, and San. The study applied the descriptive-qualitative method since the data were in the form of words, phrases, clauses, and sentences. The data sources were taken from 17 international news published in July 2023. The results revealed that, out of 235 found data, intra-sentential switching became the most occurred data regarding code switching types. In line with the reasons for code-switching, addressee specification and expressing group identity appeared dominantly in this study, followed by talking about a particular topic, interjection, indicating emotions, intention for clarifying the speech substance for interlocutors, and quoting somebody else.